Sumber, Corak, dan Metode Penafsiran dalam Kitab Tafsir Al-Muẓhiri (Analisis pada Surat An-Nur) - Irma Yanti; Ardi Rizkiana (Jurnal Syntax Admiration, 2025)
This study aims to analyze the sources, patterns, and methods of interpretation in the book Tafsir Al-Muẓhiri by Qadi Ṡanaullah Panipati, with a special focus on Surat An-Nur. Qadi Ṡanaullah Panipati is an influential scholar in India who has extensive knowledge in various Islamic disciplines, including tafsir, hadith, and fiqh. In this study, the sources of interpretation are divided into two categories, namely primary sources that include the Qur'an, hadiths, and the opinions of companions and tabi'in, and secondary sources that function to enrich the understanding of interpretation. The general method of interpretation used in this book is the tahlili method, where Qadhi Muhammad compiles the tafsir based on the order of the letters and groups the issues that have a related meaning. This study also identifies several special methods applied in interpretation, such as the explanation of makki and madani, reasonable verses, and the use of the terms "mas'alah" and "Faidah" that are characteristic of the interpretation.